Evaluation of tri-plate rapid on-farm culture system to make therapeutic decisions for mastitis cases in dairy cattle - Sajjad Ahmed; Jawaria Ali Khan; Muhammad Avais; Muhammad Imran Rashid; Muhammad Asad Ali (PLoS ONE, 2026)
The empirical use of antibiotics for clinical mastitis is a principal driver of antimicrobial resistance in dairy farming. While on-farm culture systems represent a promising strategy for targeted therapy, robust evidence of their efficacy in heterogeneous commercial settings is still needed. We conducted a randomized controlled trial across 16 commercial dairy farms. Cows with clinical mastitis (CM) were allocated to a Positive Control Treatment (PCT) group (n = 57), receiving immediate empirical intramammary (IMM) antibiotics, or a Culture Based Group (CBG) (n = 46), where treatment was directed by a tri-plate on-farm culture system after 24-hour incubation. The cows were considered experimental unit with mixed-effect models within cluster correlation. Data was statistically analyzed using chi square tests, paired t-tests and Kaplan Meier survival analysis via SPSS (version 20.0). The culture-guided protocol enabled a reduction in antibiotic use, eliminating treatment for the 45.6% of CBG cases (no bacterial growth or Gram-negative infections). The clinical cure rates between the groups (CBG 82.6% vs. PCT 75.4%) were not statistically significant (p = 0.28). Similarly, bacteriological cure rates were comparable between (PCT 71.9% vs. CBG 71.7%, p = 0.987). However, the CBG approach revealed significantly lower treatment failure rate (17.3% vs. 24.5%, p < 0.001) with a shorter median time to clinical cure (3 days vs. 7 days, p < 0.001). At the herd level, the strategy was associated with a significant increase in milk yield (+6.94 L/day, p < 0.001) and reduction in somatic cell count (−56.8%, p < 0.001). The tri-plate on-farm culture system is an effective antimicrobial stewardship tool, facilitating a substantial reduction in antibiotic use while accelerating clinical recovery and improving udder health in commercial dairy operations.